Children Rights to "Zero Hunger" and the Execution Challenges during the COVID-19 Crisis - Rahman, Nurul Hidayat binti Ab; Yasin, Redwan bin (Hasanuddin Law Review, 2022)
Zero hunger is the world's pledge under the Sustainable Development Goals 2030, which aims to end hunger, achieve food security and improve nutrition. Nevertheless, the mission had been seized as the world faced economic turndown due to the outbreak of the COVID-19 virus. The circumstances have brutally affected societies ideal living standards and raised social problems such as extreme poverty, famishment, malnutrition, and medical conditions, specifically among vulnerable children. The essential purpose of this writing is to elucidate the zero hunger goal as one of the central legal rights and identify challenges in executing it during the COVID-19 crisis. Data were collected through library studies and analyzed critically using the content analysis method. The writing finds that the progress of zero hunger is decelerated as the pandemic has caused few challenges. The paper concludes that all objectives under the SDG 2 are significant to be achieved to ensure vulnerable children survival. Thus, the paper recommends that humanitarian relief assists with food distribution among those in dire need, especially at-risk children. Furthermore, food and agricultural production must be maintained to guarantee enough food supply chain. Ultimately, every government must comply with SDG 2, specifically for the benefit of vulnerable children.